PENGARUH LOCUS OF CONTROL DAN PERILAKU INOVATIF TERHADAP WORK ENGAGEMENT MELALUI SELF-EFFICACY - Putri Desianti Ramadhan; Ari Anggarani W.P.T (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2022)
This study aims to examine and examine the effect of Locus of Control and Innovative Behavior on Work Engagement through Self-efficacy Mediation. Locus of Control and Innovative Behavior as exogenous variables, Self-efficacy as mediating variables and Work Engagement as endogenous variables. This research was conducted on employees of PT Garuda Maintenance Facility Aero Asia Cengkareng Engineering Services section with the Non Probabilty Sampling method totaling 150 respondents. The analytical method used is Structural Equation Model-Partial Least Square (SEM-PLS). The results of this study prove that Locus of Control has an effect on Work Engagement, Innovative Behavior has an effect on Work Engagement, Self-efficacy has an effect on Work Engagement, Locus of Control has an effect on Self-efficacy, Innovative Behavior has an effect on Self-efficacy, Locus of Control has an effect on Work Engagement through Self-efficacy and Innovative Behavior has an effect on Work Engagement through Self-efficacy.